Analisis Publikasi Ilmiah Dosen Terindeks Scopus Pada Fakultas Keperawatan Universitas Riau Tahun 2011-2022 - Thamrin Hasan (Media Pustakawan, 2022)
College is one of the educational institutions that incidentally can be relied upon as the producer of the most and quality scientific work. However, it is necessary to conduct a study to obtain information related to the analysis of Scopus indexed lecturer scientific publications. This study aims to determine 1) The productivity of the most scientific publications by lecturers, 2) The most cited Scientific Publications, 3) The level of collaboration in writing scientific papers, and 4) Impresum of Scopus indexed scientific publication publications. The method used is descriptive method with bibliometric analysis. The sample is 39 lecturers. Data collection techniques in the form of documentation. The data analysis technique uses the following steps: preparation, Scopus data download, tabulation, processing and manufacturing, data presentation and conclusion deflation. The results showed that 1) The productivity of most lecturer scientific publications was Yufitriana Amir's scientific publications with 11 articles, 2) The most cited and most popular scientific publications were Yufitriana Amir's articles with 83 citations, 3) The degree of collaboration of lecturers' scientific publications was 0.97 or (97 %), 4) Places where lecturers' scientific publications are published, dominantly published in the international journal Enfermeria Clinica based in Spain, namely 21 scientific works (52.5%). The conclusions of the research show that the productivity of scientific publications produced by lecturers at the Faculty of Nursing, Unri is mostly done in collaboration.